Materials resistance to corrosion by I2–HI–H2O mixtures for the realization of a sulfur-iodine plant. (11th October 2019) - Liberatore, R.; Favuzza, P.; Felici, C.; Tarquini, P.; Narducci, G.; Borruto, A.
Abstract: The substances involved in the sulfur-iodine (SI) thermochemical cycle to produce H2 by water splitting are very corrosive and may attack reactors, pumps, catalysts supports, and whatever part of the plant. This paper investigates the corrosion exerted by HI solutions in liquid, boiling, and gaseous phase at different temperatures. It shows the broadest overview of the behavior of different materials, ranging from pure metals to metallic alloys, from carbon materials to organic polymers, from ceramic materials to composite ones. Commercial nickel alloys and the effect of a specific element in their composition have here considerable attention. Regarding the composites materials, the impact of the substrate as well as the coating nature and thickness is studied, also through SEM-EDS (Scan Electron Microscope Energy Dispersive Spectroscopy) investigations. Carbon materials performed well, while most of the analyzed materials showed intergranular corrosion, pitting phenomena, and sometimes, carbide precipitation in the higher energy zones. Highlights: Corrosion resistance at I2 –HI–H2 O mixtures for SI cycle realization was analyzed. Materials exposure to liquid and gas phases at different temperatures was examined. Different materials were considered: metallic, organic, carbon, ceramic, composites. Microscopy inspection and EDS chemical analysis were used for the investigation. Carbon materials showed the best behaviour in these environments.